Humanity´s concept in Edmund Husserl: delimitation and projections - Flores Hernández, Luis (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Our proposal is focused on humanity’s concept in Husserl, attempting to delimit the corresponding family of interrelated concepts. The focus of our corpus is Die Krisis der europaïschen Wissenschaften und die transzendentale Phänomenologie (Hua VI, 1962) and the articles for the Journal The Kaizo. For Husserl, rationality is the key concept for interpreting the evolution of humanity. The purpose of the investigations, that Husserl performs in these texts, supposes the following substantial aspects: 1) What matters is the process leading to a true humanity. 2) It is essential to human life that it goes by in the form of yearning. 3) The conceptual repertory, with which Husserl investigates about humanity, constitutes an ordered sequence. 4) What is valid for mathematics, as pure science of nature, is valid analogically for a pure science of subjectivity. 5) Human becoming possesses unity and this one is given by historicity. 6) The concept of style is applied by Husserl to the human becoming. 7) A significant concept linked with the one of historicity is the concept of Heitmatlichkeit. 8) Husserl supposes an essence of rationality, with respect to which rationalism is nothing more than a deviation. 9) We distinguish four intentionalities concerning reason itself.10) Reason has unreason as negative counterpart and certain opacities impede a total transparency of reason.